Conceptual Development of Oolong Tea Packaging Design through the Kansei Engineering - Sari Zuhruf Putri Andriyani; Novi Purnama Sari (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Oolong tea is one of the tea commodities that has a distinctive taste and high global market potential. However, in Indonesia, the appeal of Oolong tea is still low compared to black tea and green tea. This may be due to the lack of packaging that can represent the character of the product and the emotional preferences of consumers. This study aims to develop a packaging design concept for Oolong tea based on Kansei Engineering by translating aspects of functionality, usability, and pleasure. A total of 30 respondents were involved in this study to conduct interviews and surveys using video stimuli as well as digital and physical packaging. The results of this exploration were analyzed using the TF-IDF method, Hierarchical Agglomerative Clustering, and K-means Algorithm. The TF-IDF analysis yielded 25 Kansei words. These were then grouped using the HAC method into four main concepts: Exclusive, Modern, Practical, and Reusable. Based on the K-means Algorithm, the Exclusive concept had the highest silhouette value. This indicates consumer preference for packaging with a luxurious and elegant feel. Based on these analysis results, it is evident that the Kansei Engineering approach, supported by statistical methods, can generate more emotional and relevant packaging concepts that can serve as references in the domestic market.